Sociodemographic and behavioural factors of adherence to the no-screen guideline for toddlers among parents from the French nationwide Elfe birth cohort - Lorraine Poncet; Mélèa Saïd; Malamine Gassama; Marie-Noëlle Dufourg; Falk Müller-Riemenschneider; Sandrine Lioret; Patricia Dargent-Molina; Marie-Aline Charles; Jonathan Y. Bernard (BMC, 2022)
Abstract Background Excessive screen time in infancy and childhood has been associated with consequences on children's development and health. International guidelines call for no screen time before age 2 years, whereas in France, the most prominent guidelines recommend no screen before age 3 years. However, data are lacking on parental adherence to the no-screen guideline for toddlers and factors of adherence in France. Using data from the French nationwide Elfe birth cohort, we estimated adherence to the no-screen guideline at age 2 years and examined related factors, including sociodemographic characteristics, parental leisure activities and screen time. Methods In 2011, 18,329 newborns and their parents were enrolled in 349 randomly selected maternity units across mainland France. At age 2 years, screen exposure of 13,117 toddlers was reported by parents in phone interviews. Data on sociodemographic characteristics, parental leisure activities and screen time were collected from both parents. Three patterns of parental leisure activities were derived by principal component analysis: literate (e.g.,reading), screen-based, and physical/artistic activities. Multivariable logistic regression models were used to examine the associations of sociodemographic characteristics, parental leisure activities and parental screen time with adherence to the no-screen guideline for toddlers. Results Overall, 1809/13,117 (13.5%) families adhered to the no-screen guideline for toddlers. Adherence was reduced with maternal age < 40 years, low parental education, single-parent household and parental migration status. After adjusting for sociodemographic characteristics, adherence to the guideline was positively associated with a parental literate activity pattern (mothers: odds ratio [95% confidence interval]: 1.15 [1.08, 1.22]); fathers: 1.15 [1.07, 1.23]) and negatively with a screen-based activity pattern (mothers: 0.73 [0.69, 0.77]; fathers: 0.81 [0.76, 0.87]). With each additional hour of parental screen time, mothers and fathers were less likely to adhere to the guideline (mothers: adjusted odds ratio 0.80 [0.77, 0.83]; fathers: 0.88 [0.85, 0.91]). Conclusions Adherence to the no-screen guideline for toddlers in France was low. Parental leisure activities and parental screen time are major factors of adherence to the no-screen guideline and could be considered in targeted public health interventions.